Crowdfunding as a tool for attracting investments in the innovative sector of the economy - M. N. Mikhailyuk; S. K. Chinazirova; R. V. Kostenko (Новые технологии)
In the context of digitalization, a special role in increasing the economic potential of the country is played by stimulating innovation and creating favorable conditions for doing business. The May decrees of the President of the Russian Federation determined the national development goals of the Russian Federation for the period up to 2024, which include an increase in the number of organizations implementing technological innovations [1]. At the same time, the priority task is to create conditions for the inflow of long-term financial resources into the economy. The solution to this problem will be facilitated not only by ensuring access for companies in the real sector of the economy to traditional channels of raising capital (bank lending, bonds and shares), but also by developing alternative investment mechanisms such as crowdfunding direct investments. The purpose of this article is to develop a concept for the creation and development of the infrastructure necessary for them by assessing the effectiveness of the current state and problems of the functioning of investment platforms in Russia. At the same time, modern methods of scientific knowledge were used: analysis, synthesis, induction, abstraction. The article substantiates the relevance of using crowdfunding as an important tool for information support of innovative projects (startups) of individuals and legal entities. The state and problems of development of investment platforms in Russia are investigated. At the same time, the factors of low popularity of investment platforms in Russia were identified. In addition, the legislative regulation of investment platforms in Russia was considered. Proposed activities for the development of investment platforms in Russia, such as: developing and conducting a strategic communication campaign, creating and maintaining a Central Repository of Public Sector Case Studies, and creating an underwriting mechanism or bridging fund for PPP projects.